HOW ARTIFICIAL INTELLIGENCE IS CHANGING EDUCATION - Narkuziyev Abdullo Abdusamat o’g’li (Research Focus International Scientific Journal, 2025)
This article shows how Artificial Intelligence is changing education by making learning more personalized, efficient, and accessible for everyone. It explains how AI helps teachers with grading and planning, supports students with tutoring and giving feedback, and helps to make lessons more interactive. It also discusses challenges like privacy, cost, and the need for teacher training. It highlights the importance of using AI responsibly and keeping a human connection in education. In short, with the right approach AI tools can help create a better learning experience for everyone and prepare students for the future.